2018
DOI: 10.1002/etc.4243
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from benthic anatoxin‐producing Phormidium are toxic to 3 macroinvertebrate taxa at environmentally relevant concentrations

Abstract: Toxin-producing cyanobacteria are increasing in rivers and streams globally, leading to growing concerns over their potential impacts on aquatic ecosystems. The present study was designed to culture field-collected Phormidium in the laboratory, identify individual species, conduct chemical analyses to identify cyanotoxins, and conduct toxicity tests to investigate the potential for this genera to impact stream health. Freshwater toxicity tests were conducted with standard US Environmental Protection Agency inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…All samples were dominated by ATX and dhATX, and not HTX and dhHTX, which contrasts with observations elsewhere: dhATX, dhHTX and HTX typically dominate in New Zealand [8, 15], and in France ATX dominates [29], although dhATX has also been detected [30]. However, Anderson et al [19] used anatoxins in crude extracts of Microcoleus cultures isolated from the Russian river in their toxicological study and dhATX comprised > 99% of the anatoxins, demonstrating that there is likely large strain to strain variability in the variants produced. The high proportion of dhATX highlights the need to use analytical methods that detect this congener (along with HTX and dhHTX) to prevent underestimation of the risk posed by benthic cyanobacteria in these systems.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…All samples were dominated by ATX and dhATX, and not HTX and dhHTX, which contrasts with observations elsewhere: dhATX, dhHTX and HTX typically dominate in New Zealand [8, 15], and in France ATX dominates [29], although dhATX has also been detected [30]. However, Anderson et al [19] used anatoxins in crude extracts of Microcoleus cultures isolated from the Russian river in their toxicological study and dhATX comprised > 99% of the anatoxins, demonstrating that there is likely large strain to strain variability in the variants produced. The high proportion of dhATX highlights the need to use analytical methods that detect this congener (along with HTX and dhHTX) to prevent underestimation of the risk posed by benthic cyanobacteria in these systems.…”
Section: Discussionmentioning
confidence: 79%
“…Extensive mats dominated by the green alga C. glomerata , are often also present at these locations, with low levels of cyanobacteria in the mats. There is uncertainty about which genera in these systems are producing toxins, although Microcoleus has been identified as an anatoxin producer in the Eel River using assembled metagenomes [18], and cultures of Microcoleus isolated from the Russian River also produce anatoxins [19]. Both toxic and non-toxic genotypes occur in the genus Microcoleus , and these genotypes can be present at varying relative abundances in environmental mats [15, 20], resulting in considerable spatial variability in anatoxin concentrations of mats within short distances.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Anderson et al. (2018) showed that acute exposure to crude Phormidium extracts containing ATX resulted in significant mortality in three macroinvertebrate taxa ( Chironomus dilutus , Ceriodaphnia dubia , and Hyalella azteca ), adding further evidence to support the presence of harmful compounds other than known toxins. Sublethal effects of benthic cyanobacteria and their cyanotoxins have not yet been investigated and this should be a priority for future research.…”
Section: Ecosystem and Human Health Impactsmentioning
confidence: 98%
“…Despite the acute neurotoxic effects of anatoxin-a, the consequence of the proliferation of anatoxins-a producing cyanobacterial biofilms on ecosystem health and aquatic organisms remains largely unknown. Despite, toxic benthic cyanobacterial mats have been associated with decreased macro-invertebrate diversity (Aboal et al, 2002), few studies have investigated the genuine toxicological effects of these compounds on aquatic organisms (Carneiro et al, 2015;Osswald et al, 2007b;Anderson et al, 2018). In some experiments performed on fishes, such as carps and goldfish, behavioural defects such as rapid opercular movement, abnormal swimming (Osswald et al, 2007a) and muscle rigidity (Carmichael et al, 1975) were observed.…”
Section: Introductionmentioning
confidence: 99%